The push and pull of radicalization and extremist disengagement: The application of criminological theory to Indonesian and Australian cases of radicalization. Issue 4 (December 2021) - Cherney, Adrian; Putra, Idhamsyah E; Putera, Vici Sofianna; Erikha, Fajar; Magrie, Muhammad Faisal
Research shows there is variability in factors that cause a person to radicalize to violent extremism. The use of the push/pull distinction has been one way in which scholars have aimed to provide clarity to the process of radicalization and extremist disengagement. However, it remains a conceptually underdeveloped distinction. In this paper, we draw on aspects of criminological theory to better understand the push and pull distinction. The paper draws on research comprising interviews with three Indonesians and two Australian individuals who have radicalized to violent extremism that is aligned with jihadist ideologies. Based on this primary data, case descriptions and narratives are provided on each individual examining pathways into and away from violent extremism. We draw on aspects of strain theory, social control, differential association, and desistance theory to understand common patterns across each case and to highlight the relative influence of various push and pull factors. Implications for theory and policy are highlighted. We also acknowledge limitations in our approach.